Encouraging students' metacognitive skills through inquiry learning - Pambudi, Galih Dimas; Winangsih, Fitri; Nunaki, Jan Hendriek; Nusantari, Elya; Damopolii, Insar (Univeritas Papua, 2022)
This study's purpose of find the inquiry-based learning effect on the metacognitive skills of high school students. This study uses a quasi-experimental method with a pre-test and post-test design. The sample size is 65 science students at a high school in Manokwari. Data analysis using the Mann Whitney test. The results showed Sig 0.00 <0.05, which means differences in metacognitive skills in the experimental and control groups. It can be concluded that there is an effect of inquiry-based learning on students' metacognitive skills.